2007
DOI: 10.1063/1.2817465
|View full text |Cite
|
Sign up to set email alerts
|

Chemical gases sensing properties of diamond nanocone arrays formed by plasma etching

Abstract: A uniform diamond nanocone array was formed by plasma etching of diamond film in a hot filament chemical vapor deposition (HFCVD) system. A surface amorphous carbon coating layer, which is formed during CH4/H2 plasma-etching process, was removed by Ar plasma in a reactive ion etching system. The hydrogenation of diamond nanocones was performed in H2 ambience by using the same HFCVD system. The air-diluted NH3 and NO2 gases sensing properties of the diamond cone arrays had been studied by using electric current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…The origin of the variation in the surface conductivity on the gas type has been the subject of a number of studies [ 14 16 ]. Overall, when oxidizing or reducing gases appear in the atmosphere, the charge exchange between the diamond and the adsorbed molecules causes an increase or a decrease in the conductance.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the variation in the surface conductivity on the gas type has been the subject of a number of studies [ 14 16 ]. Overall, when oxidizing or reducing gases appear in the atmosphere, the charge exchange between the diamond and the adsorbed molecules causes an increase or a decrease in the conductance.…”
Section: Resultsmentioning
confidence: 99%
“…15 This surface conductivity is highly dependent on the pH in aqueous media when the surface is slightly oxidised, which has led to the development of pH sensors based on those conductivity phenomena. 16 Flat 17,18 or nano-structured 19,20 hydrogenated diamond surfaces were also studied for gas sensing, where surface conductivity variations are measured upon gas exposure.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Recently, a new generation of gas sensors based on a change of surface conductivity of H-terminated intrinsic diamond upon the gas adsorption has been introduced with different sensor designs. 10,11 Our group has demonstrated that interdigitated electrodes (IDE) capped with nanostructured H-NCD are highly sensitive and selective to phosgene gas that dissolves in the surface adsorbate layer and increases surface conductivity of H-terminated diamond. 12,13 Such sensors are, in general, structurally, chemically, and electronically complex systems, and it is not straightforward to distinguish particular contributions of their overall electric response.…”
Section: ■ Introductionmentioning
confidence: 99%